Studi literatur kedudukan pelajaran Bahasa Inggris dalam Kurikulum 2013 pada jenjang sekolah dasar - Fawzy, Hamida Rizka (Maliki Interdisciplinary Journal, 2024)
English is one of the languages used in international communication. This makes the Indonesian people aware that English is very important to learn. In Indonesia itself, English language learning has been implemented for a long time. How such learning can be delivered well through a plan of education program or can be called a curriculum. The curriculum can vary from age to age. In the 2006 KTSP curriculum, learning English was categorized in local loads. Then, in the 2013 curricula, learning the English language was not offended in the local load. This study was written using a method of research into the study of how English language learning is delivered in the 2013 curriculum at the elementary school level.